THE ROLE OF FORIEGN LANGUAGES IN ENHANCING CROSS CULTURAL UNDERSTANDING - Ne’matullayeva Sevinch Komiljon qizi; Hazratqulova E’zoza Ismat qizi (TADQIQOTLAR.UZ, 2024)
ABSTRACT: Foreign languages play a pivotal role in fostering intercultural understanding by bridging cultural gaps and enhancing communication between diverse groups. Learning a foreign language goes beyond linguistic skills; it enables individuals to grasp cultural nuances, promoting empathy and mutual respect. This paper explores how foreign language education contributes to intercultural understanding, emphasizing the interplay of language, culture, and identity. By analyzing relevant studies, it demonstrates how language learners develop cultural competence, which facilitates effective cross-cultural interactions.